Earth and Beyond in Tumultuous Times - Gál, Réka Patrícia; Löffler, Petra (2021)
Earth and Beyond in Tumultuous Times offers a critical exploration of the Anthropocene concept. It addresses the urgent geopolitical and environmental questions raised by the new geological epoch. How are we to rethink landscapes, such as river deltas, oceans, or outer space? How can we create spaces for resistance and utopic dreaming? The essays and artistic interventions in this volume confront these questions by charting how space and place are constructed, deconstructed, and negotiated by humans and non-humans under conditions of globally entangled consumption, movement, and contamination.